(5x-5)=(15x-115)

Simple and best practice solution for (5x-5)=(15x-115) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-5)=(15x-115) equation:


Simplifying
(5x + -5) = (15x + -115)

Reorder the terms:
(-5 + 5x) = (15x + -115)

Remove parenthesis around (-5 + 5x)
-5 + 5x = (15x + -115)

Reorder the terms:
-5 + 5x = (-115 + 15x)

Remove parenthesis around (-115 + 15x)
-5 + 5x = -115 + 15x

Solving
-5 + 5x = -115 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-5 + 5x + -15x = -115 + 15x + -15x

Combine like terms: 5x + -15x = -10x
-5 + -10x = -115 + 15x + -15x

Combine like terms: 15x + -15x = 0
-5 + -10x = -115 + 0
-5 + -10x = -115

Add '5' to each side of the equation.
-5 + 5 + -10x = -115 + 5

Combine like terms: -5 + 5 = 0
0 + -10x = -115 + 5
-10x = -115 + 5

Combine like terms: -115 + 5 = -110
-10x = -110

Divide each side by '-10'.
x = 11

Simplifying
x = 11

See similar equations:

| h[x]=6-3x | | 8x/3=11x+9/4 | | y=sx+b | | 64-7x=11x+16 | | 4x-6x=14 | | 3x=(11x-80) | | 0.285x^2-x+2=0 | | 9x=6+6x | | -3y-6=48 | | 2x-9=19-5x | | 10y/15-28,5/15=6y/10 | | 3/4(2x+8)=2(4-4x)+17 | | 4(3-y)+8=12(3-y) | | 1/2+3/4p=1/4 | | x=1/5(90-x) | | 1/4x^2+3/4x=1 | | -3x-14=4x+14 | | 0=13/4-1/5y | | -12n=-156 | | 5x^2-68=192 | | 10/52 | | 8x-9=8(x-5) | | 1/2x+x=16 | | 4.9w-18.6=535.1 | | 4x+76=10x+12 | | 3*x^2-(2*k-3)*x-2*k=0 | | x*x-9x-70=0 | | 10k+25-5k=35 | | 3x^6+x^4-x^2=0 | | 15.8=16-0.2d | | 3x/5+9=11x-1 | | 5v(2)+32v=64 |

Equations solver categories